The War Against the Pirates British and American Suppression of Caribbean Piracy in the Early Nineteenth Century - Gough, Barry (Britain and the World, 2018)
Based on hitherto unused sources in English and Spanish in British and American archives, in this book naval historian Barry Gough and legal authority Charles Borras investigate a secret Anglo-American coercive war against Spain, 1815-1835. Described as a war against piracy at the time, the authors explore how British and American interests - diplomatic and military - aligned to contain Spanish power to the critically influential islands of Cuba and Puerto Rico, facilitating the forging of an enduring but unproclaimed Anglo-American alliance which endures to this day. Due attention is given to United States Navy actions under Commodore David Porter, to this day a subject of controversy. More significantly though, through the juxtaposition of British, American and Spanish sources, this book uncovers the roots of piracy - and suppression- that laid the foundation for the tortured decline of the Spanish empire in the Americas and the subsequent rise of British and American empires, instrumental in stamping out Caribbean piracy for good.